"Kill and Tell": The Cultural Resonance and Reverberation of Creative Nonfiction on Special Operations Forces. Issue 2 (3rd July 2018) - Pettersson, Ulrica; Ben-Ari, Eyal
Abstract : This exploratory study investigates the social and cultural significance of creative nonfiction books about Special Operations Forces. It makes three arguments. First that these volumes are constructed along the classic lines of "hero" narratives that center on the experiences of protagonists overcoming adversity and danger to succeed. Second, with the advent of "post-heroic" warfare. SOF operatives function as a sort of compensatory heroism that at once harks back to classic hero stories and places them within contemporary circumstances. Third, that the importance of cultural entrepreneurship at the base of many publications is aimed at creating and cultivating the unique reputations of SOF.